Post Keynesian theory and evidence of money supply endogeneity: a review essay - Nayan, Sabri; Kadir, Norsiah; Yusof, Abdul Hafiz; Mohamad Ali, Noor Azillah (Science and Education Centre of North America, 2015)
Money is the life-blood of any modern market-oriented economy.The level of money supply - the quantity and velocity of money circulated in such an economy would determine its health. The central issue in managing the economy is to understand how money supply is determined.The history of modern monetary economics actually has witnessed the emergence of two opposing views pertaining to the role of central bank in controlling the supply of money in an economy.A group of economists, known as monetarists, under the influence of Milton Friedman, contended that money supply in an economy is exogenously determined. Post Keynesian however holds the view that money supply is endogenously rather than exogenously determined. Examining the theory of endogenous money as well as empirical work, the present paper has found that money supply in several countries is endogenously determined.